Simplify what? I dont see anything sorry
Answer:30
Step-by-step explanation:
Since it is a right angled triangle we can apply Pythagoras principle to get y
Adjacent=a=18
Opposite=k=24
Hypotenuse =y
y=√(k^2+a^2)
y=√(24^2+18^2)
y=√(24x24+18x18)
y=√(576+342)
y=√(900)
y=30
Answer:
(2x - 5 ) (3x^2 + 5x - 7) = 6x^3 - 5x^2 - 39x - 35
The product of 2x – 5 and 3x2 + 5x - 7equal to the product of 5x - 2 and 3x2 + 5x - 7 are not equal.
Step-by-step explanation:
Product means multiplication
Product of 2x - 5 and 3x^2 + 5x - 7
(2x - 5 ) (3x^2 + 5x - 7)
= 6x^3 + 10x^2 - 14x - 15x^2 - 25x - 35
Collect like terms
= 6x^3 + 10x^2 - 15x^2 - 14x - 25x - 35
= 6x^3 - 5x^2 - 39x - 35
Product of 5x - 2 and 3x^2 + 5x - 7
(5x - 2) (3x^2 + 5x - 7)
= 15x^3 + 25x^2 - 35x - 6x^2 - 10x + 14
Collect like terms
= 15x^3 + 25x^2 - 6x^2 - 35x - 10x + 14
= 15x^3 + 19x^2 - 45x + 14
The product of 2x – 5 and 3x^2 + 5x - 7equal to the product of 5x - 2 and 3x^2 + 5x - 7 are not equal.
They both consist of different variables in their multiplier
Hope this will help you 2(-15)-1=-31
Answer:
16x²+6x+3
Step-by-step explanation:
x²+6x+3(5x²-4)+15
x²+6x+15x²-12 +15
16x²+6x+3